Is serotonin receptor HTR1B implicated in mesial temporal lobe epilepsy development? - Leal, B. (2014)
Background: Evidences from animal models have demonstrated that depletion of brain serotonin (5-HT), a neurotransmitter with a pivotal role in neurodevelopment and brain plasticity, lowers the threshold to induced seizures. It was also demonstrated that anti-epileptic drugs increase endogenous 5-HT concentrations and that 5HT-1B receptors could have an anticonvulsant role. Association studies have demonstrated that a polymorphism (rs6296) in 5HTR-1B gene may be a susceptibility factor for with temporal lobe epilepsy (TLE) development. The rs6296 G allele has been associated with decreased receptor activity. Our aim was to analyse the association between rs6296 and the development and clinical features of Mesial Temporal Lobe Epilepsy (MTLE) in a Portuguese population. Material and methods: A cohort of 121 MTLE patients (67 F, 54 M, mean age = 44 ± 11 years, age of onset = 13 ± 9 years) was compared with a cohort of 192 healthy individuals (HI). All patients had Hippocampal Sclerosis (MTLE–HS). Genotyping was performed by TaqMan real time PCR methodology. Results: rs6296 G allele was overrepresented in MTLE patients compared to controls (80.2% in MTLE vs 72.1% in HI, p = 0.029 OR = 1.561 (1.060–2.298)). We constituted 2 MTLE–HS sub-groups, according to febrile seizure antecedents and no differences in rs6596 allelic or genotypic frequencies were found. Conclusion: The rs6296 G allele may be a susceptibility factor to MTLE–HS development. Since these receptors have an anticonvulsant role, a reduction in their activity could lower the threshold for seizure development.